Bending without breaking thirteen women's stories of migration and resilience - Bichsel, Monette; Bugayong, Lenny Kaye; Fen, Fen (The Editors, 2017)
How did you get to Switzerland? The question was asked of several Filipina migrants gathered one Saturday afternoon. Stories of love and loss, of success and sacrifice, spilled out of these women in between gales of laughter, and slices of cassava cake. This book captures 13 such stories, realing the spirit of hope, survival, and endurance that any reader can find encouraging and empowering.